Exploring Core Competencies: Critical requirement for gaining Competitive Advantage in Market - Aggarwal, Nipun; Bhatnagar, Dyal (Gyan Management Journal, 2013)
When business wants to achieve competitive advantage it requires decisive capabilities which are known as core competencies. The question arises as to how to find out these core competencies, it starts when top management formulates a strategy of becoming master of complete market power. It is impossible for the management to touch each aspect of business and hence focus on core area of competence becomes critical that really affect competitive advantage. A core competency differentiates not only between firms but also inside a firm it differentiates amongst several competencies. In other words, a core competency guides a firm recombining its competencies in response to demands from the environment. Once the core competencies are recognized, a company can clearly define organizational boundaries and focus resources for maximum advantage.
Keywords: Core competencies; Learning system; Exceptionality; Valuable